Bacteremia in cirrhotic patients with upper gastrointestinal bleeding - Shih, Hsin-An; Tsai, Pei-Chuan; Wu, Kai-Hsiang; Chen, Yi-Ting; Chen, Yi-Chuan (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Increased risk of bacterial infection is common in cirrhotic patients with upper gastrointestinal bleeding (UGIB). Our study aimed to explore the association of the bacteremia with in-hospital mortality and risk factors of bacteremia in these patients. Materials and Methods: In our retrospective cohort study, we collected data for cirrhotic patients with UGIB admitted to our hospital between August 2010 and December 2010. The primary outcome was in-hospital mortality. The secondary outcome was bacteremia. A multivariate logistic regression analysis was performed to determine risk factors for mortality and bacteremia. Results: A total of 202 patients with cirrhosis presenting with UGIB at the emergency department (ED) were enrolled. Bacteremia was associated with a higher mortality rate (adjusted odds ratio [OR]: 9.7; 95% confidence interval [CI]: 1.9-50.6, p=0.007), whereas shock (systolic blood pressure <90 mmHg at ED triage) and bandemia (>0% immature neutrophils of band form) were associated with bacteremia in cirrhotic patients with UGIB (adjusted OR: 5.3; 95% CI: 2.3-12.7, p<0.0001 and adjusted OR: 4.0; 95% CI: 1.6-9.9, p=0.0003, respectively). Conclusion: Bacteremia in cirrhotic patients with UGIB is one of the major risk factors leading to in-hospital mortality. On the basis of our findings, prevention of bacteremia in cirrhotic patients with UGIB, especially in those with shock and bandemia, is important; thus, adequate antibiotic treatment is suggested. Cite this article as: Shih HA, Tsai PC, Wu KH, Chen YT, Chen YC. Bacteremia in cirrhotic patients with upper gastrointestinal bleeding. Turk J Gastroenterol 2018; 29: 164-9.